High quality financial reporting: the case of the Nairobi stock exchange - (:unkn) unknown (My University, 2015)
This thesis investigates, firstly, the meaning of the phrase “high quality financial reporting.” The use of the phrase in the academic literature, and by professional and regulatory bodies, is examined critically to contribute to a deeper understanding of the phrase.Disclosure in the annual reports of all 47 companies listed on the Nairobi Stock Exchange is examined to see if it can be described as “high quality”. “High quality disclosure” is measured in three ways: (1) a disclosure index is developed to measure compliance with International Financial Reporting Standards (this index is also used to measure disclosure in the interim report); (2) a disclosure index developed by Standard and Poor’s to measure Transparency and Disclosure is used; (3) these are compared with the scores achieved by the same annual reports in the Financial Reporting Excellence Award 2003, decided by adjudicators in Kenya.The thesis also investigates the association between selected corporate characteristics and “high quality disclosure”. Testable hypotheses are formulated based on disclosure theories and prior studies: univariate and linear regression analysis are used to test whether significant independent variables explain “high quality disclosure”, with the aim of contributing to understanding the applicability of disclosure theories to a capital market in a developing country. Interview research is employed to explore further matters related to “high quality financial reporting” in this developing country setting and to complement the quantitative analysis, so as to contribute to understanding the relevance of International Financial Reporting Standards in achieving high quality disclosure in this capital market. Conclusions are made as to the usefulness of accounting theories and other influences in explaining “high quality disclosure” by Nairobi Stock Exchange companies. A definition of “high quality disclosure” is proposed. The implications of the research, its contribution and its limitations are discussed. Suggestions for further research are presented.
Thesis Submitted in fulfilment of the requirement for the degree of doctor of philosophy department of accounting and finance University of Strathclyde. Full text thesis.
This thesis investigates, firstly, the meaning of the phrase “high quality financial reporting.” The use of the phrase in the academic literature, and by professional and regulatory bodies, is examined critically to contribute to a deeper understanding of the phrase.Disclosure in the annual reports of all 47 companies listed on the Nairobi Stock Exchange is examined to see if it can be described as “high quality”. “High quality disclosure” is measured in three ways: (1) a disclosure index is developed to measure compliance with International Financial Reporting Standards (this index is also used to measure disclosure in the interim report); (2) a disclosure index developed by Standard and Poor’s to measure Transparency and Disclosure is used; (3) these are compared with the scores achieved by the same annual reports in the Financial Reporting Excellence Award 2003, decided by adjudicators in Kenya.The thesis also investigates the association between selected corporate characteristics and “high quality disclosure”. Testable hypotheses are formulated based on disclosure theories and prior studies: univariate and linear regression analysis are used to test whether significant independent variables explain “high quality disclosure”, with the aim of contributing to understanding the applicability of disclosure theories to a capital market in a developing country. Interview research is employed to explore further matters related to “high quality financial reporting” in this developing country setting and to complement the quantitative analysis, so as to contribute to understanding the relevance of International Financial Reporting Standards in achieving high quality disclosure in this capital market. Conclusions are made as to the usefulness of accounting theories and other influences in explaining “high quality disclosure” by Nairobi Stock Exchange companies. A definition of “high quality disclosure” is proposed. The implications of the research, its contribution and its limitations are discussed. Suggestions for further research are presented.
Keywords: Financial Reaporting; Nairobi stock exchange; NSE; High quality disclosure